2011
DOI: 10.1007/s10152-011-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships among scorpaeniform fishes associated with gas platforms

Abstract: Trophic relationships between Scorpaena porcus, S. notata and Chelidonichthys lucerna collected near natural gas platforms were investigated for the first time in central Adriatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…The main resource in the diet of S. porcus is Crustacea, predominating both in relative abundance and frequency of occurrence. This result is in accordance with Castriota et al (2012) where crustaceans accounted for 89% of the relative abundance of prey and 94.5% of the frequency of occurrence. Crustacean decapods are the main dietary components of S. porcus and other scorpaenids (Harmelin-Vivien et al , 1989; La Mesa et al , 2007; Castriota et al , 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The main resource in the diet of S. porcus is Crustacea, predominating both in relative abundance and frequency of occurrence. This result is in accordance with Castriota et al (2012) where crustaceans accounted for 89% of the relative abundance of prey and 94.5% of the frequency of occurrence. Crustacean decapods are the main dietary components of S. porcus and other scorpaenids (Harmelin-Vivien et al , 1989; La Mesa et al , 2007; Castriota et al , 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This result is in accordance with Castriota et al (2012) where crustaceans accounted for 89% of the relative abundance of prey and 94.5% of the frequency of occurrence. Crustacean decapods are the main dietary components of S. porcus and other scorpaenids (Harmelin-Vivien et al , 1989; La Mesa et al , 2007; Castriota et al , 2012). These are typical scorpaenid prey items, irrespective of species, biotope or geographic zone considered (Harmelin-Vivien et al , 1989).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study demonstrated the specialized feeding behaviour of S. porcus in the SE Black Sea which was also observed in the central and north-east Adriatic Sea by Castriota et al . (2012) and Compaire et al . (2016).…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, the present study confirmed the specialist feeding strategy of S. porcus which has been reported previously by Castriota et al . (2012) and Compaire et al . (2016).…”
Section: Discussionmentioning
confidence: 95%